Exploring Frugal Buying, Social Influence, and App Behavior in Online Food Shopping in Indonesia - Widarto Rachbini; Silverius Y. Soeharso; Harimurti Wulandjani; Tiolina Evi; Erwin Permana; Suyanto Suyanto (Universitas Mercu Buana, 2023)
Objectives: This quantitative study investigates the relationships among Frugal Buying Habits, Social Influence, Task-oriented app usage, Pleasure-oriented app usage, and Digital persuasion in the context of online food shopping via delivery apps in Indonesia.Methodology: We employ an explanatory research design, testing hypotheses derived from existing literature. A purposive sampling method selects 300 active users of online food delivery apps. Structural Equation Modeling (SEM) with Smart PLS software analyzes the data.Findings: Frugal Buying Habits are associated with both Task-oriented and Pleasure-oriented app usage. Social Influence strongly impacts Digital Persuasion. Task-oriented app usage positively correlates with Digital Persuasion while Pleasure-oriented app usage does not.Conclusion: These findings highlight opportunities for app developers to cater to frugal consumers and leverage social influence, improving user experiences. Policymakers should consider regulating digital persuasion tactics for ethical practices. This research contributes to understanding online food shopping dynamics.